Internationalization of py –in-depth analysis os Sweden and LR on market selecion for small firms - Festas, Miguel Saldanha Sardinha Tavares (2021)
PY is a Portuguese SME operating in the maritime industry delivering ship parts and equipment as well as services. As the basis for decision-making, an analysis of five potential countries was carried out using both macro and industry-specific factors. Finally, a marketing plan and financial forecasts for the project were conducted and adapted to Singapore, the country chosen as the best target. The present information complements the report with a literature review on the topic of international market selection for small firms and an in-depth analysis of Sweden, one of the potential target countries, considering various distinctive dimensions.